A Grave e Generalizada Violação de Direitos Humanos enquanto Hipótese de Reconhecimento da Condição de Refugiado: Evolução Normativa e Aplicação Prática - Nunes, Bárbara Pereira de Mello (2022)
The International Refugee Regime has become an international paradigm, guiding States in the construction of legal frameworks and public policies to refugees. Through the evolution of the International Refugee Regime, it emerges, within the Declaration of Cartagena, the possibility of granting refuge in the American region because of a massive violation of Human Rights, which represented a shift in the paradigm, increasing the scope of protection to this group of vulnerable people, paradigm also adopted by the Brazilian Refuge Law, which provided for the possibility of granting refuge based on a serious and widespread violation of Human Rights, which later served as a model for other South American countries to also publish their respective Refuge Laws with the provision of the expanded definition of refugee. This dissertation aims to present the evolution of the Serious and Widespread Violation of Human Rights as a legal hypothesis for granting refuge, analysing the context of its creation and consolidation at the international and regional spheres, as well as its treatment by the Brazilian and other South America countries legislation, including their procedures and organs responsible for the refuge granting analysis, as well as the study of the institute’s practical application in the national context, specifically analysing the Syrian case, as well as the paradigmatic case of Venezuela.